Comparison of P-Possum and Esas (Emergency Surgery Acuity Score) For Prediction of 30-Day Mortality in Patients Undergoing Emergency Laparotomy - Ibn E Ali, Paras; Ilyas, Sohail; Ashraf, Sohaib; Zafar, Hamayal; Kazmi, Farwa; Siddiqui, Ubaid Ullah (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the validity of the Portsmouth Physiological and Operative Severity Score for the enumeration of Mortality and morbidity (P-POSSUM) and Emergency Surgery Acuity Score (ESAS) scoring system and compare the positive predictive value of both in predicting 30 days’ mortality in patients undergoing emergency laparotomy. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Surgery and Department of Accident and Emergency, Combined Military Hospital Rawalpindi, Pakistan from Aug 2021 to Mar 2022. Patients and methods: A total of 210 patients were enrolled in the study, with 30-day post-operative mortality as the primary outcome of interest. P-POSSUM and ESAS scores were calculated for all patients upon presentation to the surgical emergency. A cutoff of 19 for ESAS and 63 for P-POSSUM was used to predict 30-day post-operative mortality in emergency laparotomy patients. Results: The observed mortality rate among the recruited patients was 9.5%. The mean age was 46.24±11.13 years, with 62.4% of the population being male. Among those who died within 30 days of follow-up, the majority were aged over 50 years (p=0.002) and predominantly male (p=0.460), with most having ileal or jejunal perforation. The AUROC for ESAS in predicting 30-day post-operative mortality was 0.974, while for P-POSSUM it was 0.885. Conclusion: ESAS and P-POSSUM can both be employed in emergency surgical situations. As ESAS can be calculated pre-operatively, it should be preferred over P-POSSUM.